Correlation of Alpha-Fetoprotein Levels with ThreePhase Contrast CT-Scan Finding in Hepatocellular Carcinoma Patients at Dr. Mohammad Hoesin General Hospital Palembangin 2022 – 2023 - Nainggolan, Florence Tania; Suprianto, Imam; ., Legiran (The Indonesian Society for Digestive Endoscopy, 2025)
Background: Hepatocellular carcinoma (HCC) is the primary liver tumor, accounting for 90% of liver tumor cases. Currently, laboratory tests are needed to monitor tumor progression, predict prognosis, and determine appropriate therapy without radiological examinations, one of which is Alpha-Fetoprotein (AFP). This study aims to determine the correlation between AFP levels and three-phase contrast CT-Scan findings in HCC patients at Dr. Mohammad Hoesin General Hospital Palembang.Methods: This was a cross-sectional design observational analytic study, using secondary data from medical records that included patient demographics, AFP, ALT, AST, direct bilirubin, indirect bilirubin, and three-phase contrast CT-Scan findings covering nodule size, nodule number, and metastasis in HCC patients treated at Dr. Mohammad Hoesin General Hospital Palembang from January 2022 – December 2023, meeting inclusion and exclusion criteria. Data were analyzed using SPSS version 22. Results: A total of 71 samples met the inclusion and exclusion criteria. Univariate analysis showed the majority were male (83.1%), aged 50–59 years (35.2%), with elevated ALT (59.2%), AST (94.4%), direct bilirubin (91.8%), indirect bilirubin (54.1%), AFP ≥200 ng/mL (77.5%), nodule size ≥30 mm (87.3%), multiple nodules (67.6%), and no extrahepatic metastasis (74.6%). Bivariate analysis showed a significant correlation between AFP levels and nodule size on three-phase contrast CT-Scan (p-value = 0.031).Conclusion: There is a significant correlation between AFP levels and three-phase contrast CT-Scan findings in HCC patients at Dr. Mohammad Hoesin General Hospital Palembang in 2022–2023.